MANAJEMEN PERANCANGAN ELEKTRONIC FILLING SYSTEM (E-FILLING) UNTUK PENDATAAN KEPENDUDUKAN MENGGUNAKAN METODE ALFRED - Eka Satria Wibawa; Eko Siswanto (Universitas Sains dan Teknologi Komputer, 2021)
Kelurahan is one of the government agencies which is the spearhead in administrative services to the wider community, the Kaliwungu subdistrict is an administrative part of the Kaliwungu sub-district, Semarang Regency which is located at Jl. Raya Ampel –Simo KM 8, in the service and processing of population administration data in the Kaliwungu village, they still use the conventional method, namely the data is still stored separately in books, this of course has weaknesses such as when looking for data records, difficulties in making reports population that cannot be obtained immediately and the process of data collection and storage of population archive data that is still stored and recorded manually. This research was conducted using the Research & Development Method through the system design stages which were validated by experts and product prototypes that were field tested by involving users. Making a prototype of an electronic filing system (e-filing) system application using the ALFRED method approach to analyze the system, the software used using Microsoft Visual Basic 6.0 as a design medium and as a programming language, and a SQL Server database as a storage medium. The final result of this research is a product prototype of a filing system using an electronic filing system (e-filing) which has been declared to be functioning properly so that it can produce useful information for the archiving process up to the stage of making reports, which can be done quickly and accurately in accordance with established procedures. already exist, making it easier to re-access archives and provide public services with accurate and integrated information